2022
DOI: 10.31234/osf.io/2ezfj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

[PREPRINT] Mind the Machines: Applying Implicit Measures of Mind Perception to Social Robotics

Abstract: Beyond conscious beliefs and goals, automatic cognitive processes shape our social encounters, and interactions with complex machines like social robots are no exception. With this in mind, it is surprising that research in human-robot interaction (HRI) almost exclusively uses explicit measures, such as subjective ratings and questionnaires, to assess human attitudes towards robots - seemingly ignoring the importance of implicit measures. This is particularly true for research focusing on the question whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…At the same time, the mismatch between explicit and implicit measures found in the present study is in line with the recent work in the field of Human-Robot Interaction. Li and colleagues examined the mind perception of robots using a manipulated version of the IAT (MP-IAT) and explicit mind perception rating [82]. As there was no correlation between constructs, the authors suggested that implicit and explicit measures might be related but potentially independent concepts that require independent assessment.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the mismatch between explicit and implicit measures found in the present study is in line with the recent work in the field of Human-Robot Interaction. Li and colleagues examined the mind perception of robots using a manipulated version of the IAT (MP-IAT) and explicit mind perception rating [82]. As there was no correlation between constructs, the authors suggested that implicit and explicit measures might be related but potentially independent concepts that require independent assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Others have investigated people’s responses to robots by examining their explicit impressions of robot partners ( Kaplan, 2004 ; Becker-Asano et al, 2010 ; Flandorfer, 2012 ; Mandell et al, 2017 ; Dubois-Sage et al, 2023 ). Although some studies investigated whether humans would explicitly or implicitly ascribe a mind to a robot on a perceptual level ( Spatola and Wudarczyk, 2021 ; Li et al, 2022 ), limited studies have explored whether people would interact with a robot as if it has a mind. In this study, we adopted methods from social cognitive studies focused on human-human interaction, and tested whether people will spontaneously take the perspective of a robot in a way similar to how they do with another human.…”
Section: Introductionmentioning
confidence: 99%